Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, dan Ukuran Perusahaan Terhadap Manajemen Laba - Geo Putri; Dirvi Surya Abbas; Mulyadi Mulyadi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The purpose of This study aims to identify and examine the effect of tax planning, deferred tax expense and firm size on earnings management practices. The sample in this study is the consumer goods and industrial sub-sector companies listed on the Indonesia Stock Exchange with an observation period of 2015 to 2019. The results of this study indicate that tax planning has no effect on earnings management, deferred tax expense affects earnings management and firm size affects earnings management.